Day of civil resistanse - Anušauskas, Arvydas (Genocidas ir rezistencija, 2002)
May 14th will henceforth be commemorated as Day of Civil Resistance. 30 years ago, the drastic form of political protest – political suicide – chosen by the nineteen-year-old Romas Kalanta on 14 May 1972 resonated deeply in Lithuanian society, especially among the youth. In the garden of Kaunas Musical Theatre, he poured petrol on himself and, as witnesses testify, after shouting “Freedom for Lithuania!”, set himself on fire. The event caused panic among LKP and KGB officials. The chekists hurried to bury Kalanta secretly themselves before the announced burial time. The people who gathered for the funeral were outraged by the KGB’s arbitrariness. Mass marches began, during which political slogans were chanted. Mass demonstrations, violence, and arrests lasted two days. More than 400 people were arrested, and Kalanta became a symbol of civil resistance.
Keywords: Soviet regime; antisoviet resistance; youth resistance; Romas Kalanta